A CASE OF PARAPLEGIA DUE TO THORACAL SPINAL EPIDURAL ABSCESS - Serpil Savaş,; Memduh Kerman,; Başak Öğüt, (Archives of Rheumatology, 2003)
Spinal epidural abscess (SEA) is an uncommon spinal infectious disease. Clasically, SEA presents with severe back pain, local tenderness, and fever, progressively worsening radicular symptoms followed by neurologic deficits. The delayed diagnosis is associated with significant morbidity and mortality. In this case report, a patient who became paraplegic because of thoracal SEA is presented.